2009
DOI: 10.1016/j.biopsych.2008.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Medial Orbitofrontal Cortex Gray Matter Is Reduced in Abstinent Substance-Dependent Individuals

Abstract: Background-Chronic exposure to drugs of addiction induces cellular adaptations in orbitofrontal cortex (OFC) and associated limbic-prefrontal pathways that may underlie abuse-related behavior. A propensity to make risky decisions in spite of substantial negative consequences may be mediated by medial OFC dysfunction in substance dependent individuals (SDI). We tested the hypothesis that medial OFC gray matter (GM) volume would be lower in SDI compared to controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
163
0
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(193 citation statements)
references
References 39 publications
25
163
0
5
Order By: Relevance
“…Por otra parte, sabemos que esta impulsividad, sobrevenida tras la fase de consumo, ya sea por efecto directo de la sustancia o mediada por otros factores, como el estrés (Perry y Carroll, 2008), es en buena parte reversible (Forcada, Pardo y Bondía, 2006;Bankston et al, 2009) y se corresponde con una mejoría gradual en el funcionamiento cognitivo en función del tiempo de abstinencia, del tipo de droga consumida (Selby y Azrin, 1998) y de los problemas psicosociales concurrentes (Bates, Voelbel, Buckman, Labouvie y Barry, 2005), a pesar de que la persistencia de las neuroadaptaciones provocadas por la administración repetida de drogas puede prolongarse en el tiempo, específicamente la del cortex órbito-frontal, encargado del control de las conductas tex órbito-frontal, encargado del control de las conductas tex impulsivas (Tanabe et al, 2008). Por su parte, la IF parece corresponderse con una disposición más estable de funcionamiento frontal, caracterizado por una mayor velocidad de procesamiento de estímulos relevantes en el contexto de un comportamiento orientado a metas, y correlaciona significativamente con rasgos como la Excitabilidad Exploratoria, relacionada con curiosidad, tendencia a escanear el ambiente en busca de estímulos novedosos, rapidez y flexibilidad de procesamiento cognitivo ; Pedrero Pérez y Rojo Mota, 2008).…”
Section: Discussionunclassified
“…Por otra parte, sabemos que esta impulsividad, sobrevenida tras la fase de consumo, ya sea por efecto directo de la sustancia o mediada por otros factores, como el estrés (Perry y Carroll, 2008), es en buena parte reversible (Forcada, Pardo y Bondía, 2006;Bankston et al, 2009) y se corresponde con una mejoría gradual en el funcionamiento cognitivo en función del tiempo de abstinencia, del tipo de droga consumida (Selby y Azrin, 1998) y de los problemas psicosociales concurrentes (Bates, Voelbel, Buckman, Labouvie y Barry, 2005), a pesar de que la persistencia de las neuroadaptaciones provocadas por la administración repetida de drogas puede prolongarse en el tiempo, específicamente la del cortex órbito-frontal, encargado del control de las conductas tex órbito-frontal, encargado del control de las conductas tex impulsivas (Tanabe et al, 2008). Por su parte, la IF parece corresponderse con una disposición más estable de funcionamiento frontal, caracterizado por una mayor velocidad de procesamiento de estímulos relevantes en el contexto de un comportamiento orientado a metas, y correlaciona significativamente con rasgos como la Excitabilidad Exploratoria, relacionada con curiosidad, tendencia a escanear el ambiente en busca de estímulos novedosos, rapidez y flexibilidad de procesamiento cognitivo ; Pedrero Pérez y Rojo Mota, 2008).…”
Section: Discussionunclassified
“…A recent meta‐analysis of 9 studies and 296 alcohol dependent individuals found significantly reduced prefrontal gray matter (GM) volumes, including anterior cingulate cortex (ACC) [Xiao et al, 2015], with frontal cortical GM volume being negatively associated with lifetime alcohol use [Taki et al, 2006]. Prefrontal GM volumes were similarly reduced in cocaine dependent individuals, including in orbitofrontal cortex (OFC) [Rando et al, 2013; Tanabe et al, 2009], anterior prefrontal cortex [Rando et al, 2013] and ACC [Connolly et al, 2013], the latter associated with years of drug use [Connolly et al, 2013]. …”
Section: Introductionmentioning
confidence: 99%
“…Specifically, damage to the orbitofrontal-subcortical circuit disrupts behavioral inhibition (Cummings, 1995) and lesions to lateral and ventral OFC, but not the mPFC, disrupt reversal learning (Bissonette et al, 2008). Human alcoholics often display symptoms similar to patients with OFC damage, including deficits in behavioral inhibition (Verdejo-Garcia et al, 2006) and measures of impulsivity/perseveration (Hill et al, 2009;Tanabe et al, 2009). Chronic alcohol exposure has also been shown to disrupt behavioral flexibility in experimental models of alcohol dependence.…”
Section: Introductionmentioning
confidence: 99%